Distal end of Double-J ureteral stent position on ureteral stent-related symptoms: A systematic review and meta-analysis - Bao, Xingjun; Sun, Fengze; Yao, Huibao; Wang, Di; Liu, Hongquan; Tang, Gonglin; Wang, Xiaofeng; Zhou, Zhongbao; Wu, Jitao; Cui, Yuanshan (Frontiers in Surgery, 2022)
Background Most patients suffer from ureteral stent-related symptoms (USRS) caused by indwelling ureteral stents. Nevertheless, various medications to alleviate discomfort as well as novel stents are continually being developed, and in recent years, some researchers have believed that proper intravesical stent placement can relieve USRS. Objective To determine appropriate intravesical ureteral stent position may alleviate USRS. Methods Up to May 1, 2022, the PubMed, Embase, Scopus and Web of Science databases were thoroughly searched, and two independent reviewers included relevant studies that met the PICO (Patient, Intervention, Comparison, Outcome) criteria. Studies methodological quality were assessed by ROB2 and ROBINS-I. Ureteral stent symptom questionnaire (USSQ), international prostate symptom score (IPSS) and quality of life (QoL) was used to quantify the USRS. According to intravesical ureteral stent position, Group A was defined as the contralateral group, that is distal end of ureteral stent crossed the bladder midline, whereas Group B was classified as ipsilateral group, meaning stent end did not cross the midline. Results Six studies incorporating a total of 590 patients were eligible. In terms of USSQ score, the meta-analysis showed that contralateral group was associated with a significant increase in USSQ total (MD, 17.55; 95% CI, 12.04 to 23.07; P < 0.001), urinary symptoms (MD, 2.74; 95% CI, 0.48 to 5.01; P = 0.02), general health (MD, 4.04; 95% CI, 2.66 to 5.42; P < 0.001), work performance (MD, 1.36; 95% CI, 0.75 to 1.98; P < 0.001) and additional problems (MD, 0.89; 95% CI, 0.47 to 1.32; P < 0.001) scores while not associated with a significant increase in body pain (MD, 3.13; 95% CI, −0.19 to 6.44; P = 0.06) and sexual matters (MD, 1.01; 95% CI, −0.03 to 2.06; P = 0.06). As for IPSS, although no significant differences in IPSS total (MD, 2.65; 95% CI, −0.24 to 5.54; P = 0.07) or voiding symptoms (MD, −0.84; 95% CI, −3.16 to 1.48; P = 0.48) scores were found, ipsilateral group was associated with a significant decrease in storage symptoms (MD, 1.92; 95% CI, 0.91 to 2.93; P = 0.0002). Furthermore, ipsilateral group was linked to a significant decrease in QoL score (MD, 1.00; 95% CI, 0.18 to 1.82; P = 0.02). Conclusion This meta-analysis proven that correct intravesical stent position was critical, and patients with stents crossing the midline experienced more severe USRS than those who did not. Further high-quality randomized controlled trials are needed to corroborate our findings.